2012
DOI: 10.1007/s11033-012-1858-7
|View full text |Cite
|
Sign up to set email alerts
|

TNFAIP1 interacts with KCTD10 to promote the degradation of KCTD10 proteins and inhibit the transcriptional activities of NF-κB and AP-1

Abstract: The broad-complex, tramtrack, and bric-a-brac/poxvirus and zinc finger domain-containing protein tumor necrosis factor, alpha-induced protein 1 (TNFAIP1) was first identified as a gene whose expression can be induced by the tumor necrosis factor alpha. Some studies showed that TNFAIP1 may function in DNA replication, apoptosis and human diseases. However, the definite functions and the mechanisms of TNFAIP1 are poorly known. In this study, we performed a yeast two-hybrid assay and used TNFAIP1 as the bait to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…The cDNA fragments encoding full-length GSK-3β and β-TrCP were cloned into pCMV-Myc vector, and the truncated APC (1-453 a.a.) and (454-1020 a.a.) fragments were ligated into pCMV-Myc vector. The pCMV-Myc-Ubiquitin plasmid was described previously [40]. The pCMV-HA-p53 plasmid was constructed as described [41].…”
Section: Methodsmentioning
confidence: 99%
“…The cDNA fragments encoding full-length GSK-3β and β-TrCP were cloned into pCMV-Myc vector, and the truncated APC (1-453 a.a.) and (454-1020 a.a.) fragments were ligated into pCMV-Myc vector. The pCMV-Myc-Ubiquitin plasmid was described previously [40]. The pCMV-HA-p53 plasmid was constructed as described [41].…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that NF-κB-mediated transcriptional upregulation of TNFAIP2 by the Epstein-Barr virus oncoprotein, LMP1, promotes cell motility in NPC (20). However, few studies have shown that TNFAIP1 inhibits the transcriptional activities of NF-κB (25). In the present study, we found that knockdown of TNFAIP1 downregulated the expression of NF-κB at the translational level in OS cells, suggesting that TNFAIP1 may promote the progression of OS through activation of the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the results of our immunohistochemical study were contrary to expectation: the expression level of KCTD10 was higher in patients with a favorable outcome (Figure 4, Table 2). Recently, Hu et al reported that KCTD10 inhibited the transcriptional activities of NF-κB and AP-1 [26]. These inhibitory effects were strongly promoted by treatment with a proteasome inhibitor, as KCTD10 expression is regulated through ubiquitination and degradation [26].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hu et al reported that KCTD10 inhibited the transcriptional activities of NF-κB and AP-1 [26]. These inhibitory effects were strongly promoted by treatment with a proteasome inhibitor, as KCTD10 expression is regulated through ubiquitination and degradation [26]. Therefore, further investigation of KCTD10, especially in vivo experiments, would be of interest from the view point of biomarker research and novel therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%